Symbol of Antigone: Selfless or Selfish? (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2022)
After reading Sophocles’ play Antigone, one may believe that Antigone selflessly defied an anti-burial law by burying her brother because she loved him and wanted to honor the gods. However, this paper examines the various instances before and after the burial in which Antigone constantly seeks external validation and attention from her peers, thereby asserting that Antigone selfishly wanted to become a symbol of martyrdom.For additional context, listen to the author's reflection on the piece below.